Financial Statement Fraud, Financial Performance, Sustainability Disclosure, and Firm Value in Food and Beverage Companies - Ni Kadek Widyantari; Evi Yuniarti; Eksa Ridwansyah (International Journal of Accounting and Management Information Systems, 2026)
Purpose: This study examines how financial statement fraud, financial performance, and sustainability disclosure affect firm value, with firm age controlled, in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during 2022-2024. Methodology: This quantitative study used annual reports, audited financial statements, sustainability reports and official company publications. Purposive sampling selected 32 of the 103 companies, yielding 96 initial firm-year observations. The data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing using IBM SPSS Statistics 25. Results: Financial statement fraud, measured using the F-score, has a negative but insignificant effect on firm value. Return on assets has a positive and significant effect, whereas sustainability disclosure has an insignificant effect. Collectively, the independent variables significantly explain firm value after controlling for firm’s age. Conclusions: Investors respond more strongly to realized profitability than to analytical fraud-risk indicators or the quantity of sustainability disclosures. Limitations: This study covers one manufacturing subsector, a three-year period, and proxy-based measurements that do not directly capture confirmed fraud or disclosure quality. Contributions: This study refines signaling theory by showing that signal visibility, credibility, and financial materiality determine whether information is incorporated into market valuation. Practically, they emphasize profitability, reporting integrity, and decision-useful sustainability disclosure. Novelty: This study distinguishes market reactions to latent fraud-risk signals, realized financial signals, and disclosure-based sustainability signals within a recent post-pandemic subsector context.